1985
DOI: 10.1524/ract.1985.38.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Radiolytic Oxidation of Am (III) to Am(V) in NaCl Solutions

Abstract: A mericium /Radioly tic oxidation of km ¡Laser photoacoustic spectroscopy Abstract The autoradiolytic oxidation of 241 Am (III) to 241 Am (V) in 5 M NaCI solution has been investigated by pulsed laser-induced photoacoustic spectroscopy and spectrophotometry. In the presence of a moderate dose rate (1 Ci/L) of own α-radiation, the Am (III) ions are quantitatively oxidized to Am (V) within a week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…The oxidation becomes completed within a week [17][18][19]. Radiolysis reactions induced by α-radiation transfer the NaCl solution to a strongly oxidizing medium.…”
Section: Am(v) Hydrolysis In Saline Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation becomes completed within a week [17][18][19]. Radiolysis reactions induced by α-radiation transfer the NaCl solution to a strongly oxidizing medium.…”
Section: Am(v) Hydrolysis In Saline Solutionmentioning
confidence: 99%
“…While carrying out experiment, it is found that a-radiation induced radiolysis reactions in concentrated Nad solutions become significant, resulting in the oxidation of Am (111) to Am(V) [17][18][19]. For this reason the hydrolysis reactions of Am(V) have been also investigated in a selected saline solution.…”
Section: Introductionmentioning
confidence: 99%
“…9 shows autoradiolytic oxidation of Am(III) in 3M NaCl. The Am (III) hydroxide dissolves oxidatively in the solution of high oxidation potential created by a-radiolysis of chloride solution [ 14]. The resulting solution contains only the AmOÎ ion at first and turns out to form carbonate species by absorbing CO2 from air.…”
Section: Speciation In Pure Solventsmentioning
confidence: 99%
“…In the case of americium(III) hydroxide in presence of NaCl (5 mol/1) also an appreciably higher rate of oxidation to Am(V) was observed than in water [8]. It was explained by the influence of radiolysis of the NaQ solution.…”
Section: Resultsmentioning
confidence: 91%